2015
DOI: 10.1175/mwr-d-14-00274.1
|View full text |Cite
|
Sign up to set email alerts
|

Central and Eastern U.S. Surface Pressure Variations Derived from the USArray Network

Abstract: Large-magnitude pressure signatures associated with a wide range of atmospheric phenomena (e.g., mesoscale gravity waves, convective complexes, tropical disturbances, and synoptic storm systems) are examined using a unique set of surface pressure sensors deployed as part of the National Science Foundation EarthScope USArray Transportable Array. As part of the USArray project, approximately 400 seismic stations were deployed in a pseudogrid fashion across a portion of the United States for 1-2 yr, then retrieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 75 publications
2
19
0
Order By: Relevance
“…Figure shows a decrease in GW activity detected by the TA from 2011 to 2012—paralleling what is seen in the AIRS data. This is consistent with a study by Jacques et al () that observed a decline in mesoscale pressure perturbations on TA sensors after August 2011. The 2012 data also indicate that despite the overall lower GW occurrence rate, a decline in activity can still be observed from the western edge of the network (located where the GW activity was concentrated in 2011) to the eastern edge of the network.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Figure shows a decrease in GW activity detected by the TA from 2011 to 2012—paralleling what is seen in the AIRS data. This is consistent with a study by Jacques et al () that observed a decline in mesoscale pressure perturbations on TA sensors after August 2011. The 2012 data also indicate that despite the overall lower GW occurrence rate, a decline in activity can still be observed from the western edge of the network (located where the GW activity was concentrated in 2011) to the eastern edge of the network.…”
Section: Discussionsupporting
confidence: 93%
“…A prominent region of mesoscale pressure perturbations was also found in this area by Jacques et al (, ). This feature was particularly prominent during the spring and summer months (Jacques et al, ). Mesoscale pressure perturbations over the Great Central Plains with large amplitudes (>100 Pa) and areal extents (>10,000 km 2 ) were tracked by Jacques et al (); their eastward motion and speeds are consistent with the GW phase velocities and propagation azimuths in this study.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The direction and velocity of wave propagation can be derived using arrays of three or more instruments (Blanc et al, 2014;Farges et al, 2003;le Pichon et al, 2002). Larger arrays of barometers such as those used in the USArray network have been used to detect convectively generated GWs at the surface with time periods of 2-6 hr (Balachandran, 1980;de Groot-Hedlin et al, 2017;Jacques et al, 2015). However, the microbarometer network used in de Groot-Hedlin et al (2017) only covers parts of the mainland United States.…”
Section: Introductionmentioning
confidence: 99%